PEMANFAATAN INTERFACE PORT PRINTER UNTUK PENGONTROLAN PENGGUNAAN PERALATAN LISTRIK RUANGAN - yani Prabowo (Bit (Fakultas Teknologi Informasi Universitas Budi Luhur), 2011)
The development of increasingly advanced technology to bring the impact of changes in every part of life. For example, at present many high-rise buildings make use of technological advances in various fields, such as for security from theft and robbery, safety from fire hazards and various other purposes. In this research, designed a system that can be used to control the use of various devices and electronic equipment connected to electricity in a building, such as lights, fans and other equipment to be monitored or controlled in its use. But the authors only specialize in monitoring and controlling the problem because the lights for other electronic equipment can also be simulated by the lamp, if the light is on means the tool is active and if the lights go out such a device is not active. Language of controlling light by using the printer port was already there before, namely by using low-level language programs such as Assembler or a high-level language Pascal, and also limited to only be able to control 8 lights. In the present study was developed by the circuit using a comparator (comparator) 4 bits, then the number of floors of the building limited to a maximum 15 floors, this number is obtained from the calculation of binary numbers is 24 (2 rank of 4 = 16) after deducting 1 due to address 0000 / $ 0 is used as initialization. By using the parallel port data, amounting to 8 bits can be used to control 15 floors with each floor there are 8 dots / lights so the total points that can be controlled is 120 points / lights.Keywords: interface, controlling light, paralel ports